+0  
 
-1
118
3
avatar

πŸ’π’™πŸ’+πŸπŸπ’™πŸ‘βˆ’πŸ—π’™πŸβˆ’πŸπŸ•π’™

 May 31, 2021

Best Answer 

 #2
avatar+438 
+3

not even that hard to factor:

\(4x^4+12x^3-9x^2-27x\\=x(4x^3+12x^2-9x-27)\\=x(4x^2(x+3)-9(x+3))\\=x(4x^2-9)(x+3)\\=\boxed{x(2x+3)(2x-3)(x+3)}\)

btw if you didn't do it by hand then how did you do it?

 May 31, 2021
 #1
avatar+347 
-2

I think what you meant to paste is 

4x3+12x3-9x2-27x

 

I mean, I'm not doing it by hand because that would be a pain so you can just take this a leave.

 

(x-1)(2x+3)(x-2)(2x-3)

 

Yay!

 May 31, 2021
 #2
avatar+438 
+3
Best Answer

not even that hard to factor:

\(4x^4+12x^3-9x^2-27x\\=x(4x^3+12x^2-9x-27)\\=x(4x^2(x+3)-9(x+3))\\=x(4x^2-9)(x+3)\\=\boxed{x(2x+3)(2x-3)(x+3)}\)

btw if you didn't do it by hand then how did you do it?

textot  May 31, 2021
 #3
avatar+347 
0

magic.

Varxaax  May 31, 2021

45 Online Users

avatar